A theory of rhetoric about the role of affections in the oratorical art - Ulčinaitė , E. (Psichologija, 1981)
Ancient rhetoric (Aristoteles, Cicero, Quintilianus) paid great attention to the emotional effect of the oratorical art, analysed the possibilities and ways to evoke affections. The role of affections was emphasized by the l7th c. rhetoric. The ideas of N. Caussinus, S. Lauxmin and A. Juglaris, the famous rhetoricians of the l7th c., are discussed in the article. The conclusion is drawn that the teaching of affections in the oratorical art has made a great impact on psychology and philosophy.
Keywords: rhetoric; oratorical art; emotions; affections